(untitled) - Mangieri, John N. (San Francisco, 2003)
Now in its second edition, the Yale Assessment of Thinking is a 69-item, self-scored test that will help you to determine your proficiencies in the three domains of thinking: reasoning, insight, and self-knowledge. Research studies have determined that these three areas are crucial to a person's ability to solve problems, to reach decisions, and to think creatively. This proven instrument will give you the information you need to become aware of your proficiency levels in each of these domains and, within them, your internal and external cognitive processes. Once you are cognizant of your thinking skills, you can take steps to significantly enhance your ability to think.
Keywords: Reasoning,Self-perception,Insight,Self-evaluation; Ability testing,Testing,Testing